Nodal reliability and nodal price in deregulated power markets - Yi, Ding (Nanyang Technological University, 2008)
Electric utilities are experiencing restructuring throughout the world. The main objectives of power system restructuring are to introduce competition in the power industry and to provide more choices to market participants in the way they trade electricity and ancillary services. The direct consequences of the restructuring are the economical separation of conventional vertically integrated utilities into independent generation, transmission and distribution companies. Economic segregation and service unbundling have changed the mechanism of conventional system planning and operations. In restructured power systems, customers could select their power and reserve providers to satisfy their price and reliability expectations. Customer choices have changed the fundamental of system reliability management. The reliability techniques used in a conventional power system cannot be directly applied in the new environments. Moreover electricity pricing in a restructured power system has become a major problem due to the changes in market structure. It is therefore necessary to develop the new techniques and to improve the existing techniques for the planning and operation of restructured power systems. This essay focuses on reliability and price issues of restructured power systems. The reliability and pricing issues in the restructured electric power systems have been investigated in the research work. The existing techniques for the reliability evaluation of the conventional power system have been studied. The optimal dispatch techniques in the competitive electric power systems have been introduced. The techniques, which are based on reliability network equivalent techniques and pseudo-sequential simulation techniques to evaluate reliability indices for a restructured power system with a bilateral market structure have been proposed. A technique to evaluate nodal prices and nodal reliabilities considering the correlation between price and reliability in a restructured power system with Poolco market model has been developed. The reliability network equivalents and the improved optimal power flow models to evaluate reliabilities and prices in a restructured power system with the hybrid market structure have been presented. The nodal price decomposition technique has been investigated and extended to precisely analyze the influence of system outage to the nodal prices. Based on the nodal price decomposition technique a penalty schema for reducing electricity price volatility has been proposed. A technique to determine optimal reserve structure of a restructured power generating system has been developed to incorporate system economics in reliability evaluation.